Chelerythrine inhibits HSV-1 infection by suppressing virus binding to the cells - Ziwei Hu; Chaowei Zhang; Jianfeng Zhong; Hao Hu; Chenyang Li; Yunshi Zhao; Lu Wang; Liang Ye; Cong Yan; Mingzhong Wang; Qinchang Zhu; Bo Wen; et al. (Elsevier, 2023)
Objective: Herpes simplex virus type 1 (HSV-1) is a worldwide pathogen and mainly puts immunocompromised patients at higher risk of various complications. This research aims to demonstrate the antiviral activity of chelerythrine (CHE), an alkaloid compound derived from the traditional Chinese medicine Mcleaya cordata, towards the HSV-1 F strain. Methods: Bioassay-guided fractionation was carried out in order to isolate the antiviral compound CHE. The plaque reduction assay was used to evaluate the antiviral activity of CHE. The combination of quantitative PCR (qPCR) and western blot was used to elucidate whether CHE interferes with viral DNA synthesis, followed by time-of-addition assay to examine which steps of HSV-1 infection CHE affected. The immunofluorescent assay and transmission electron microscopy assay were performed to further analyze the intracellular localization and the ultrastructural features of HSV-1 virions with the treatment of CHE. The binding affinity in CHE to targeted viral glycoprotein was investigated by surface plasmon resonance (SPR) assay and docking simulation. Results: CHE displayed a significant antiviral effect against HSV-1 at 0.312 to 2.5 µM with a viral titer reduction of 29.38% to 61.02%. CHE had an EC50 value of 1.78 µM against HSV-1, and the selectivity index (SI) for CHE was 4.07. Additionally, CHE inhibits ICP0 expression in the immediate early stage of infection, which further affected the early stage of infection, and subsequent viral replication. Results of the SPR assay showed that CHE had strong-binding affinity to gB with a KD value of 7.80 × 107 M, while gD with a value of 1.18 × 106 M. TEM revealed that CHE can clearly inhibit the virion release. In silico experiments further confirmed that CHE had low binding free energy in the activity sites of gB and gD. Conclusion: This study revealed that CHE directly targeted viral gB or gD as a potent glycoprotein inhibitor, which suggested that CHE could be a virus entry inhibitor for HSV-1 treatment.